Revenue determinants in tourism market - Mohebi, Mohammad; Abdul Rahim, Khalid (Science Publications, 2010)
Malaysian tourism industry has been growing considerably in recent years. The number of tourist arrivals has grown by 25% during 2006-2008. In comparison with Thailand and Singapore, Malaysia has more tourist arrivals but it has earned less income. The purpose of the study was to determine the major factors affecting inbound tourism expenditure in Malaysia. Approach: A panel data set for 14 origin countries, from 1998-2009 has been used to estimate tourism expenditure using gravity model. Results: The results of the expenditure model suggest that the Malaysian price index and distance have negative impact while per capita income of origin countries and Malaysian per capita income have positive impact on tourism expenditure. Conclusion: The own price elasticity indicates in short run that the tourism expenditure was inelastic to price. But in the long run tourism expenditure in Malaysia was elastic and potential tourists are more sensitive to the price changes. The lagged dependent variables high coefficient (0.78) was represents that, our expectation has been right about consumer constancy to the destination. Based on the results, Singapore was a complementary destination meanwhile Thailand and Australia are substitute destination for Malaysia and finally SARS crisis negatively affected the tourism revenue.